Differences in response to a low altitude football training camp supplemented with additional hypoxic training - Hamlin, M.; Manimmanakorn, A.; Manimmanakorn, N.; Simpson, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Living and training at altitude is a popular training method for athletes, however, there is considerable individual variation in subsequent sea-level performance improvement where some athletes adapt successfully, while others do not adapt and fail to improve. Since such training is expensive, time consuming, and normally requires considerable logistical planning, coaches and athletes do not want unsuccessful altitude training experiences. Therefore, the aim of this study was to investigate possible physiological measures that might recognise athletes that respond positively to altitude training compared to those that do not. METHODS: This longitudinal study included 20 male football players (20.6 ± 1.1 years, 173.9 ± 4.8 cm, 67.7 ± 8.3 kg, mean ± SD) who undertook an 8-week training camp at 825 m above sea-level (Khonsan, Chaiyaphum Province, Thailand). Players were also supplemented with intermittent hypoxic training via a hypoxicator (Altitude Training Systems, Australia) 15 min/day 3 times/week at FIO2 of 0.15 while cycling at an exercise intensity between 100-120 W. Based on the players 2800-m running performances between baseline and 14 days post training camp, players were separated into responders (improved by 10.7 ± 8.1%, mean ± 95% CI, n=14) and non-responders (decreased by 6.1 ± 12.8%, n = 6). Changes in the 2800 m run performance along with other physiological variables (resting heart rate, arterial oxygen saturation, heart rate variability, haematology and blood lactate) from the 3 trials (baseline, 1, and 14 days post training camp) and standard deviations representing the between-and within-subject variability were estimated using a mixed modelling procedure (Proc Mixed) in the Statistical Analysis System (Version 9.3, SAS Institute, Cary, North Carolina, USA). The effect size statistic (ES) was also calculated. RESULTS: Compared to baseline, the responders had a lower heart rate at 1 (-4.6 ± 2.7 bpm, Effect Size = 1.2) and 14 days (-6.7 ± 3.3 bpm, ES = 1.7) post training camp, whereas the non-responders resting heart rate did not change substantially. Compared to the non-responders, the responders had higher pNN50 at 1 (12.2 ± 11.5, p = 0.04, ES = 1.6) and 14 days (10.1 ± 11.7, p = 0.09, ES = 1.4) post training camp. As a result of the training camp, the responders decreased their LF/HF ratio at day 1 (-1.1 ± 0.6, p < 0.01, ES = 1.0) and day 14 post camp (-0.9 ± 0.6, p < 0.01, ES = 0.8), whereas the non-responders LF/HF ratio moved in the opposite direction (0.8 ± 0.9 and 0.9 ± 0.9), with large effect sizes found between groups (ES = 1.7-1.8). Between-group differences in other variables measured were not substantive. CONCLUSION: Reduced resting heart rate and increased cardiac parasympathetic tone was associated with improved run performance after the altitude training camp and may be used to differentiate athletes that respond to altitude training compared to those that do not.